Green synthesis of selenium based N-heterocyclic carbene compounds; structural, in-vitro anticancer and molecular docking studies. (October 2021) - Hayat, Khizar; Tariq, Umaira; Wong, Qin Ai; Quah, Ching Kheng; Majid, Aman Shah Abdul; Nazari V, Mansoureh; Ahamed, Mohamed. B. Khadeer; Iqbal, Muhammad Adnan; Tirmizi, Syed Ahmed
Abstract: Benzimidazolium salts (3−6) were synthesized as stable N -Heterocyclic Carbene (NHC) precursors and their selenium-NHC compounds/Selenones (7−10) were prepared using water as a solvent. Characterization of each of the synthesized compounds was carried out by various analytical and spectroscopic (FT-IR, 1 H-, 13 C NMR) methods. X-ray crystallographic analyses of single crystals obtained for salts 3 and 5 were carried out. Synthesized salts and their Se- NHC s were tested in-vitro for their anticancer potential against Cervical Cancer Cell line from Henrietta Lacks (HeLa), Breast cancer cell line (MDA-MB-231), Adenocarcinoma cell line (A549) and human normal endothelial cell line (EA.hy926). MTT assay was used for analysis and compared with standard drug 5-flourouracil. Benzimidazolium salts (3−6) and their selenium counter parts (7−10) were found potent anticancer agents. Salt 3–5 were found to be potent anticancer against HeLa with IC 50 values 0.072, 0.017 and 0.241 μM, respectively, which are less than standard drug (4.9 μM). The Se- NHC s (7–10 ) had also shown significant anticancer potential against HeLa with IC 50 values less than standard drug. Salts 3, 4 against EA.hy926, compounds 3, 5, 6, and 10 against MDA-MB-321, and compounds 4, 10 against A-549 cell line were found more potent anticancer agents with IC 50 values less than standard drug. Molecular docking for (7−10) showed their good anti-angiogenic potential having low binding energy and significant inhibition constant values with VEGFA (vascular endothelial growth factor), EGF (human epidermal growth factor), COX1 (cyclooxygenase-1) and HIF (hypoxia inducible factor). Graphical Abstract: Graphical abstract shows the summary of the article that proposed compounds were first of all studied computationally. After checking the interaction of these compounds with various proteins through molecular docking, these compounds were synthesised in the laboratory and their biological potential was checked experimentally. ga1 Highlights: Organoselenium compounds and their salts were designed, and synthesized. IR NMR, and X-ray crystallography characterization of synthesized compounds was done. Molecular docking was carried to observe possible interaction of Se-NHC compounds with Proteins.